Investigation of a hydrometallurgical process route to recover metals from waste printed circuit boards - Chirume, Blessing Hellen (Department of Chemical Engineering, 2020)
The loss of valuable materials such as base and precious metals is increasing due to the increase in waste electronic and electric waste (WEEE). Most of these metals in WEEE are on the printed circuit boards (PCBs). This study aims to compare different pre-treatment methods to recycle copper from PCBs using a hydrometallurgical process. In order to obtain a uniform/consistent sample across all the tests done, similar custom-made PCBs with 55.45% wt copper were used to compare different parameters. Pre-treating the PCBs is the first stage of the process and it is done to liberate metals which are then dissolved in subsequent leaching stages. Eight different pre-treatment methods were explored. The pre-treated PCBs were then leached under similar conditions in a diagnostic leach test in order to get an indication of the effectiveness of the pre-treatment. Copper recoveries corresponding to each of the pretreatment methods were compared. In addition to recovery, other factors such as time taken for copper recovery, material losses incurred, practicability, environmental impact, health and safety were used to compare the pre-treatment methods. A score was given for each factor and the average was used to choose the optimal pre-treatment method. A method where the PCBs were cut into 1.5 cm x 2 cm pieces and then soaked in 2 M NaOH at 40 °C for 24 hours had the highest average score. This pre-treatment method was then used to prepare PCBs that were used for test work done with the aim to optimise copper leaching. The influence of total ammonia concentration, liquid to solid ratio and choice of ammonium salt used in the buffer system, were investigated in the copper leaching optimisation stage of this thesis. Using ammonium carbonate resulted in lower recoveries compared to ammonium sulphate in the diagnostic leach test. Increasing the ammonia concentration to 7M did not have a significant effect on the copper recovery. Decreasing the liquid to solid ratio from 20ml/g to 10ml/g resulted in a slower rate of recovery. The optimal leaching conditions were found to be; 750 ml mixture of 4 M NH3, 2 M (NH4)2SO4, 100ppm CuSO4 at 25 °C and 500 rpm using the optimal pre-treatment method for the PCBs.